Current structure and future challenges of the agricultural sector - Majah-Leah V. Ravago; Arsenio M. Balisacan (University of the Philippines, School of Economics (UPSE), 2015)
This chapter provides an overview of the patterns, composition, policies and institutional environment that have influenced the performance of the agriculture sector in recent years. The focus is on the changing dynamics of supply and demand for agriculture as a whole and for key commodity groups and livestock in the context of a growing economy, urbanization, and regional market integration. It concludes with a discussion of the policy and institutional challenges to making agriculture a key pillar in the country's pursuit of inclusive growth, poverty reduction, and sustainable development.
Keywords: Q10; Q17; Q18; 330; Philippine agriculture; structural transformation; poverty